SHRIMP geochronology of a mylonite zone on Tonagh Island: characterisation of the last high-grade tectonothermal event in the Napier Complex, East Antarctica - Crowe,WarwickA.; Osanai,Yasuhito; Toyoshima,Tsuyoshi; Owada,Masaaki; Tsunogae,Toshiaki; Hokada ,Tomokazu (National Institute of Polar Research, 2002)
P(論文) Tonagh Island within the highest-grade zone of the Napier Complex, East Antarctica, consists of a strongly layered sequence of quartzofeldspathic gneiss, mafic granulite and ultramafic gneiss subdivided into five lithostratigraphic units by major NE-SW to E-W trending steeply-dipping D_6 shear zones. D_6 shear zones cut the principal foliation defined by D_1 and D_2 structures associated with the ultrahigh-temperature metamorphism. Zircons from two mylonite samples with moderate NE pitching mineral lineations within a D_6 shear zone and a D_6 mylonite and ultramylonite sample from within high strain zones that have an overprinting sub-horizontal mineral lineation were analyzed. All samples have anhydrous mineral assemblages with a late textural association of biotite, which formed pre- to syn- a secondary overprinting high temperature mylonitic fabric. Zircons in all samples contain a structureless zone that constitutes most of the grain area and commonly have a relict discordant, oscillatory-zoned core. The core may be obscured to the extent where only a structureless or an indistinct remnant remains These internal patterns are consistent with recrystallisation and annealing processes resulting in resetting of the U-Pb system during mylonitsation involving possibly three events between ca. 2550 Ma and ca. 2470 Ma. The timing of D_6 mylonitisation between ca. 2470-2550 Ma on Tonagh Island requires an earlier timing for UHT metamorphism. This is consistent with regional models that attribute UHT metamorphism to pre- ca. 2550 Ma tectonothermal events in the Napier Complex. departmental bulletin paper